Important Considerations in the Initial Clinical Evaluation of the Dysmorphic Neonate. (August 2015) - Smpokou, Patroula; Lanpher, Brendan C.; Rosenbaum, Kenneth N.; Ikuta, Linda; Zukowsky, Ksenia
<x xml:space="preserve">Abstract</x> Background: The approach to clinical evaluation of the dysmorphic neonate can be challenging and multifaceted. It requires specialized knowledge of rare diagnoses and awareness of immediate versus long-term needs for the newborn and the family. Purpose: This review summarizes important considerations in the initial evaluation of genetic syndromes, which can present in the neonatal period with variable aspects of dysmorphism. Methods: An overview of the literature in this area is provided. Findings/Results: Several overlapping areas of concern for working with this population are addressed, including communication with the family, fundamentals of the physical examination, common genetic disorders, syndromes, as well as palliative care and end of life decision making for the newborn in the context of family needs. Implications for Practice: The initial approach for the neonatal practitioner needs to focus on various aspects of the newborn's care, including medical stabilization, determining whether immediate laboratory or imaging studies are needed, careful physical examination with particular attention to detail, appropriate and timely communication with the family, and knowledge of various specific aspects of rare diseases. Implications for Research: More research is needed to better understand how to best support the newborn born with dysmorphia or a rare disease. Particular attention needs to be focused on strategies to best support the family who is often in crisis during the neonatal period.